Characterization of transport from the Asian summer monsoon anticyclone into the UTLS via shedding of low potential vorticity cutoffs - Clemens, Jan; Ploeger, Felix; Konopka, Paul; Portmann, Raphael; Sprenger, Michael; Wernli, Heini (Atmospheric Chemistry and Physics, 2022)
Air mass transport within the summertime Asian monsoon circulation provides a major source of anthropogenic pollution for the upper troposphere and lower stratosphere (UTLS). Here, we investigate the quasi-horizontal transport of air masses from the Asian summer monsoon anticyclone (ASMA) into the extratropical lower stratosphere and their chemical evolution. For that reason, we developed a method to identify and track the air masses exported from the monsoon. This method is based on the anomalously low potential vorticity (PV) of these air masses (tropospheric low PV cutoffs) compared to the lower stratosphere and uses trajectory calculations and chemical fields from the Chemical Lagrangian Model of the Stratosphere (CLaMS). The results show evidence of frequent summertime transport from the monsoon anticyclone to midlatitudes over the North Pacific, even reaching the high-latitude regions of Siberia and Alaska. Most of the low PV cutoffs related to air masses exported from the ASMA have lifetimes shorter than 1 week (about 90 %) and sizes smaller than 1 % of the Northern Hemisphere (NH) area. The chemical composition of these air masses is characterized by carbon monoxide, ozone, and water vapour mixing ratios at an intermediate range between values typical for the monsoon anticyclone and the lower stratosphere. The chemical evolution during transport within these low PV cutoffs shows a gradual change from the characteristics of the monsoon anticyclone to characteristics of the lower stratospheric background during about 1 week, indicating continuous mixing with the background atmosphere.